Culture, Kinship and Genes
XII, 272 p.
Keywords: The first comprehensive attempt to explore the issues raised by genetic counselling across cultures. It will be of interest to health professionals and to students and lecturers in the social, behavioural and political sciences and in genetics, medicine and nursing. The meaning and relevance of kinship and ethnicity in the context of genetic disease, cultural issues that have arisen in practice, including the influence of the lay public's beliefs about inheritance and the wider social and political context of genetics and genetic disease are all explored in depth.